Case Report: How whole-genome sequencing-based cell-free DNA prenatal testing can help identify a marker mhromosome - Kleinfinger, Pascale; Brechard, Marie; Luscan, Armelle; Trost, Detlef; Boughalem, Aicha; Mylene Valduga,; Serero DR, Stéphane; Costa, Jean-Marc; Lohmann, Laurence (Frontiers in Genetics, 2022)
A supernumerary marker chromosome (SMC) is a structurally abnormal chromosome that cannot be characterized by conventional banding cytogenetics. Marker chromosomes are present in 0.075% of prenatal cases. They are associated with variable phenotypes, ranging from normal to severely abnormal, and the prognosis is largely dependent on the results of further cytogenomic analysis. Here, we report the identification and characterization of a marker chromosome following prenatal screening in a 39-year-old pregnant patient. The patient had a normal first trimester ultrasound but was high-risk for fetal chromosome anomalies based on the results of maternal serum parameters. Chorionic villus sampling was performed, and analysis of chorionic villi revealed the presence of two identical marker chromosomes. In the interest of a rapid identification of the markers, we performed noninvasive prenatal testing (NIPT) together with chorionic villus sampling. A pericentromeric 29 Mb duplication of chromosome 20: dup (20) (p13q11.21) was identified and thereafter confirmed by targeted metaphasic FISH. Whole-genome sequencing-based NIPT was instrumental in rapid characterization of the SMCs and allowed us to obviate the need for multiple expensive and time-consuming FISH analyses.